Assessing the Impact of Supply Chain Financing Mechanisms on Advancing Corporate Social Responsibility: A Comparative Literature Review - Irawan, Dadang; Christy Patricia, Mia; Santoso, Seger (Journal of Economic and Leadership, 2024)
This qualitative literature review explores the role of supply chain financing (SCF) mechanisms in promoting corporate social responsibility (CSR) through a comparative analysis of eight key studies. The findings reveal that SCF mechanisms, such as reverse factoring, dynamic discounting, and green financing, significantly enhance CSR adoption by mitigating financial constraints and fostering sustainable practices across supply chains. However, the effectiveness of these mechanisms varies by industry, region, and organizational context, underscoring the need for tailored approaches. The review highlights the potential of advanced technologies, including blockchain and AI, to increase transparency and scalability. Limitations include a focus on developed economies and the lack of standardized metrics for assessing SCF’s impact on CSR. This study provides critical insights for future research and practical applications of SCF to align financial and sustainability objectives.